Recapitalization, bailout, and long-run welfare in a dynamic model of banking - Andrea Modena (Leibniz Institute for Financial Research SAFE, 2020)
This paper studies the link between bank recapitalization and welfare in a dynamic production economy. The model features financial frictions because banks benefit of a cost advantage at monitoring firms and face costly equity issuance. The competitive equilibrium outcome is inecient because agents do not internalize the e↵ects banks' capitalization over the allocation of capital, its price and, in turn, firms investments. It follows, individual recapitalizations are sub-optimal and bailout policies may benefit social welfare in the long-run. Bailouts improve capital allocation in states where aggregate banks are poorly capitalized, therefore enhancing their market valuation, fostering investments, and stabilizing the economy recovery path.
urn:nbn:de:hebis:30:3-552282
Keywords: D51; G21; 330; banks; bailout; general equilibrium; financial frictions; recapitalization; welfare